Analisis Etika Profesional terhadap Risiko Keamanan pada Sistem OpenClaw - Muhammad Faiqul Umam Dzunnuroeni; Muhammad Zaky Ramadhan; Evy Nurmiati (Repeater : Publikasi Teknik Informatika dan Jaringan, 2026)
This study aims to evaluate the implementation of the built-in security model in a local installation of the OpenClaw autonomous agent and to analyze its implications for information technology (IT) professional ethics. The study employed a qualitative method using a single-case study approach. Primary data were collected through direct simulation experiments comparing secure and insecure configurations within an isolated environment. The results indicate that OpenClaw incorporates native security controls based on a single trust boundary and provides adequate security auditing capabilities. The system also includes data protection mechanisms that minimize the risk of misuse when operated according to the recommended configuration. However, configuring the network to be publicly accessible (0.0.0.0) without authentication violates the principle of least privilege and significantly increases the risk of unauthorized access. These findings demonstrate that vulnerabilities in self-hosted autonomous agents are not solely attributable to technical weaknesses in the system but also reflect failures in adhering to IT professional ethics. Therefore, responsibility is clearly shared between developers and IT practitioners. Developers are responsible for providing adequate security mechanisms, while IT professionals have an ethical obligation to maintain system security, protect user privacy, and ensure that security configurations are implemented in accordance with established best practices.